Biosynthesis of Copper Oxide Nanoparticles using Starch of Maize and It’s Antimicrobial Activity against Opportunistic Pathogens - Mouruj A. Al-Aubydi (Journal of Global Pharma Technology, 2018)
Copper oxide nanoparticles were synthesized by thermal green synthesis method using basically starch of maize, CuSO4.5H2O, with an abundance quantity of ammonia solution as stabilizing and alkalinity agent, the reaction was completed at 200 ͦC. The formation of black solution was represented the creation of CuO nanoparticles. Finally, after precipitation, washing by deionized water and ethanol and drying, CuO nanoparticles are obtained as black powder. The synthesized copper oxide nanoparticles were characterized via various techniques, included ultraviolet –visible (UV-visible) spectrophotometry, X-ray diffraction (XRD), fourier transform infrared spectroscopy analysis(FTIR) and transmission electron microscopy (TEM).All the analysis showed that the nanoparticles were very constant, pure, globular shape as well as average crystallite measure is 9.8nm. The particles diameter size was ranging from 47.41nm to 109.49nm. However, the average distribution (d50) is71.17nm.Antibacterial CuO nanoparticles activity of different concentrations were tested against four strains of pathogenic Gram-negative bacteria Escherichia coli, Klebsiella pneumonia, Pseudomonas aeruginosa and Gram-positive bacteria Staphylococcus aureus. The results showed that different concentration of CuO nanoparticles have been significant increasing effect in inhibiting of a bacterial growth compared with the control for both types of bacterial isolates. Also,it was found that all isolates appeared high level of resistance against most usable antimicrobial agents, while these resistance were decreased in case of combination with CuO NPs. Thus there is a synergistic effect between CuO NPs and antimicrobial agents. Keywords: Copper oxide nanoparticles, X-ray diffraction, Starch, Antibacterial activity.